The cornerstones of corporate strategies in Slovenia and Croatia (Research Note) - Matej Lahovnik (Journal for East European Management Studies, 2004)
In our study, we managed to include companies involved in six different industries. Diversification is the most frequently used corporate strategy. Our study reveals that 43.3% of companies diversified through external means, 26.7% diversified through internal means, while 30% diversified through both internal and external methods. Retrenchment strategies are relatively unpopular because retrenchment seems to imply failure. The orientation of most top management towards growth strategies has resulted in a strong preference for acquisitions and joint ventures. 90.3% of companies are expanding their operations internationally. In our paper, we also examine the motives for developing a specific corporate strategy. Special attention is given to the core competencies and skills that have proved to be the cornerstones of the competitive advantages of companies. – – In unserer Studie gelang es uns, Firmen zu beschreiben, die in sechs unterschiedlichen Industriebereichen tätig sind. Diversifikation ist die am häufigsten eingesetzte korporative Strategie. Unsere Studie belegt, daß 43,3% von den Firmen durch die externen Mittel variiert werden, 26,7% variieren durch interne Mittel, während 30% durch die internen und externen Methoden variieren. Einschränkungsstrategien sind verhältnismäßig unbeliebt, weil wie es scheint, Einschränkung Ausfall ankündigt. Die Lagebestimmung des meisten oberen Managements in Richtung Wachstumstrategien hat eine starke Präferenz für Erwerb und Joint Ventures ergeben. 90,3% der Firmen erweitern ihre Betriebe international. In unserem Beitrag überprüfen wir auch die Motive für die Gestaltung einer spezifischen korporativen Strategie. Besondere Aufmerksamkeit wird den Kernkompetenzen und -fähigkeiten gewidmet, die als Grundsteine der Firmenwettbewerbsvorteile fungieren.
Keywords: 650; Company; corporate strategy; growth; transition